Going National: Ciudadanos from Catalonia to Spain. Issue 4 (1st October 2016) - Rodríguez Teruel, Juan; Barrio, Astrid
Abstract: Ciudadanos, a party founded in Catalonia in 2006, has recently acquired a major role in the Spanish political system. This article examines why it was formed almost ten years ago and how it has evolved since; its ideological principles and policy menu; the party organisation and leadership; the main determinants of its vote, and the structure of opportunities faced by the party in the 2015 general election. It considers Ciudadanos in two different contexts ‒ Catalonia and all Spain ‒ and in two different 'time zones': before 2014, when the party was mainly a regional force, and after that date. In each context, the party seems to have responded to the unsatisfied demands resulting from the double electoral market failure of the last decade in Spain and Catalonia.